2012
DOI: 10.1016/j.fct.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of Canova homeopathic medicine in cyclophosphamide-treated non-human primates

Abstract: Our results demonstrated that Canova treatment minimizes cyclophosphamide myelotoxicity in C. apella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…Importantly, the low white blood cell counts in healthy animals is expected, because there is no need to destroy pathogens (Salami, 2018;Duan et al, 2019); similarly, this is important for maintaining high levels of globulins, the animal's humoral defense system. Other studies reported an increase in the number of lymphocytes when the animals received homeopathic medicines (Leal et al 2012;Abud et al 2006;Burbano et al 2009;Cesar et al 2008), unlike what we reported here. We believe that the lower degree of bacterial contamination in the mammary gland was responsible for the reduction of lymphocytes and neutrophils, because these are the first lines of immune defense against pathogens (Cohn and Hirsch, 1960).…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, the low white blood cell counts in healthy animals is expected, because there is no need to destroy pathogens (Salami, 2018;Duan et al, 2019); similarly, this is important for maintaining high levels of globulins, the animal's humoral defense system. Other studies reported an increase in the number of lymphocytes when the animals received homeopathic medicines (Leal et al 2012;Abud et al 2006;Burbano et al 2009;Cesar et al 2008), unlike what we reported here. We believe that the lower degree of bacterial contamination in the mammary gland was responsible for the reduction of lymphocytes and neutrophils, because these are the first lines of immune defense against pathogens (Cohn and Hirsch, 1960).…”
Section: Discussioncontrasting
confidence: 99%
“…In spite of its wide range of medical benefits, it can induce many destructive effects on patients under its treatment (Khan et al 2014). Cyclophosphamide (CP) has the ability to induce genetic alterations (Ahmadi et al 2008;Leal et al 2012). It was used in the current study as a positive genotoxic agent.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Different studies have suggested that homeopathic preparations, such as Canova (Parana, CU, Brazil), can activate macrophages, stimulate the production of ROS and positively affect some cytokines that play an important role in inflammatory processes. [16][17][18][19][20][21] The objective of this research was to evaluate the effect of homeopathic preparations with pathogenic strains of Vibrio, Phosphoricum acidum and Silicea terra on the expression of interleukin-1β (IL-1β), MyD88 and piscidin genes and the antioxidant activities of superoxide dismutase (SOD) and catalase (CAT) of weaning stage (WS-30 days post-hatching [dph]) and early juveniles (EJ-60 dph) of S. rivoliana.…”
Section: Introductionmentioning
confidence: 99%